Assessment of the Service Innovation System in the Region of Bucharest-Ilfov - Alina-Elena Iosif; Laurențiu Tăchiciu (Amfiteatru Economic Journal, 2016)
Competitive economies display a pattern of regional clusters and networks, where innovation is stimulated by intensive interaction among industries and where knowledge intensive services play an important role in novelty creation and diffusion. In order to catch up with the most competitive regions, the region of Bucharest-Ilfov needs to develop a service-inclusive innovation system, which in turn requires an adequate policy mix. The main aim of this paper is to provide an assessment of the service innovation system in the Bucharest-Ilfov region, by confronting its current performance with the regional innovation policy context. On one hand, we characterize the performance of the service innovation system in accordance with the methodology and the data provided by the European Service Innovation Scoreboard. On the other hand, using desk research and in-depth interviews with experts, we investigate the service innovation policy mix on conceptual grounds provided by the literature regarding the typology of service innovation policy approaches. We find that the policy measures supporting innovation that are available in the Bucharest-Ilfov region are not specifically targeted to regional development priorities and are predominantly technology oriented. Policies are not systemic and ignore the potential of knowledge intensive business services to be a driver for innovation in the region. This paper highlights the stakes of adopting a coherent regional innovation policy, designed systemically, and exploiting the full potential of knowledge-based services. Being aware of the current state of service innovation within the region and its potential, the stakeholders may benefit of the recommendations included within the paper.
Keywords: O32; O38; R58; 330; service innovation; knowledge intensive business services; innovation policy; regional development